Fine tuning style and precision: Adapting directive citations to Finnish statutes - Piehl, Aino (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
When transposing EU directives into national laws, Finnish drafters usually alter the wording of the directive. This paper describes these modifications and offers some insights into the reasons behind them. The study is based on a corpus of Finnish versions of EU directives and of Finnish laws that transpose those directives.